THE INFLUENCE INTOLERANCE OF UNCERTAINTY ON CYBERCHONDRIA IN EARLY ADULT INTERNET USERS - fadila, novi; Dwatra, Free Dirga (Causalita, 2024)
This study aims to determine the effect of intolerance of uncertainty on cyberchondria in early adult internet users. This research uses quantitative methods. The sample collection technique used in this study was purposive sampling. This study had a sample of 138 early adults in Padang City. The data collection method in this study used a questionnaire distributed via a google form link. The research instrument used is the cyberchondria scale that has been compiled which refers to the Cyberchondria Severity Scale (CSS) which is made based on the dimensions described by Mcelroy & Shevlin (2014) which were then modified by Aulia (2019) to become 30 items with a reliability of 0.899 and uses an uncertainty intolerance scale that refers to the IUS-12 (Intolerance of Uncertainty Scale- Short Form) which is made based on aspects that have been developed by Carleton et al. (2007) as many as 12 items, which were then adapted into Indonesian by Bagaskara (2009) and have a reliability of 0.735. The results of data analysis obtained using simple linear regression analysis show that Ho is rejected and Ha is accepted with an r-square value of 0.189 which indicates that there is a positive influence between intolerance of uncertainty on cyberchondria The higher the intolerance of uncertainty felt by individuals, the higher the cyberchondria in individuals, and vice versa the lower the intolerance of uncertainty in individuals, the lower the cyberchndria that occurs in individuals.